O desenvolvimento emocional na Educação Especial: um estudo sobre a avaliação pedagógica para a Sala de Recursos Multifuncionais - Ribeiro, Cíntia Kamila de Bona (2023)
This research is based on the principles of Vigotski's Historical-Cultural Theory, and sought to investigate the teaching discourse, revealed in pedagogical evaluations in the school context, sent to the Special Education sector of the Regional Education Center of Cascavel, belonging to the structure of the State Secretariat of Education (SEED) of the State of Paraná, whether emotional development is recorded by them, how this recording occurs and what understanding of this aspect of development is expressed by these teachers. This assessment is developed in accordance with the guiding documents of the State Department of Education in the State of Paraná (SEED). The research was documentary, and its corpus was based on documents relating to pedagogical assessments carried out by Special Education teachers. 107 evaluation reports made available by the NRE for the research were analyzed, covering the years 2016 to 2019, developed by 30 teachers, who worked in 14 schools in the investigated network, looking for the references made by teachers in relation to emotional aspects. To analyze the data, the methodology of Cores of Meaning proposed by Aguiar and Ozella (2006) was used, which allowed the analysis of evaluation reports forming Pre-indicators, Indicators and Cores of Meaning in a dialectical movement of synthesis. The five Cores of Meaning resulting from the analysis are: Behavioral aspects, Aspects linked to learning, Aspects linked to socialization, Emotional aspects and Aspects linked to the indication of a medical report. The research also reveals that emotions appear in assessments only as a finding without any reflection on their importance in emotional development. The need for teachers to be prepared to observe and consider the socialization, emotional and behavioral aspects involved in the learning processes is highlighted, maintaining the focus on the development of students' theoretical thinking, overcoming the conceptions that stigmatize based on the diagnoses presented in clinical/medical reports. To this end, public policies are necessary that provide teachers with space in their working hours, in order to guarantee continuous in-service training, enabling them to maintain their own mental health in order to consider the emotional development of their students.